Mens Rea in Anti-Corruption Law: Challenges and Approaches in Regional Legal Frameworks - Triana Dewi Seroja; Emiliya Febriyani; Vicko Taniady; Febri Jaya; Antony Antony (Syura: Journal of Law, 2026)
This study examines the implications of mens rea in anti-corruption laws across Indonesia, Thailand, and the Philippines, focusing on the philosophical basis behind corruption as a breach of the social contract. The objective is to assess how the mens rea concept in these countries' legal frameworks impacts the effectiveness of anti-corruption enforcement. Through normative legal research, the study analyzes key legal norms, particularly focusing on inconsistencies in mens rea provisions that may hinder the full potential of anti-corruption laws. The findings reveal that while Indonesia’s framework incorporates severe penalties and reverse burden of proof, its inconsistency in defining corrupt intent weakens its deterrence power. Thailand’s legal framework, although more consistent, lacks provisions for willful blindness, while the Philippines suffers from fragmented laws and ambiguous mens rea standards. The study highlights the need for a more coherent mens rea framework to strengthen anti-corruption enforcement and align legal systems with public expectations for government integrity and accountability.